Severity of OSAS, CPAP and cardiovascular events: A follow‐up study. (3rd March 2018) - Baratta, Francesco; Pastori, Daniele; Fabiani, Mario; Fabiani, Valerio; Ceci, Fabrizio; Lillo, Rossella; Lolli, Valeria; Brunori, Marco; Pannitteri, Gaetano; Cravotto, Elena; De Vito, Corrado; Angelico, Francesco; et al.
Abstract: Background: Previous studies suggested obstructive sleep apnoea syndrome (OSAS) as a major risk factor for incident cardiovascular events. However, the relationship between OSAS severity, the use of continuous positive airway pressure (CPAP) treatment and the development of cardiovascular disease is still matter of debate. Study objectives: The aim was to test the association between OSAS and cardiovascular events in patients with concomitant cardio‐metabolic diseases and the potential impact of CPAP therapy on cardiovascular outcomes. Methods: Prospective observational cohort study of consecutive outpatients with suspected metabolic disorders who had complete clinical and biochemical workup including polysomnography because of heavy snoring and possible OSAS. The primary endpoint was a composite of major adverse cardiovascular and cerebrovascular events (MACCE). Results: Median follow‐up was 81.3 months, including 434 patients (2701.2 person/years); 83 had a primary snoring, 84 had mild, 93 moderate and 174 severe OSAS, respectively. The incidence of MACCE was 0.8% per year (95% confidence interval [CI] 0.2‐2.1) in primary snorers and 2.1% per year (95% CI 1.5‐2.8) for those with OSAS. A positive association was observed between event‐free survival and OSAS severity (log‐rank test; P = .041). A multivariable Cox regression analysis showed obesity (HR = 8.011, 95% CI 1.071‐59.922, P = .043), moderate OSAS (vs non‐OSAS HR = 3.853, 95% CI 1.069‐13.879, P = .039) and severe OSAS (vs non‐OSAS HR = 3.540, 95% CI 1.026‐12.217, P = .045) as predictors of MACCE. No significant association was observed between CPAP treatment and MACCE (log‐rank test; P = .227). Conclusions: Our findings support the role of moderate/severe OSAS as a risk factor for incident MACCE. CPAP treatment was not associated with a lower rate of MACCE.